Reguły antydopingowe w prawie międzynarodowym - Piechota, Rafał (Studia Iuridica Toruniensia, 2010)
<!--[if gte mso 9]> <![endif]--> The way in which anti-doping legislation came into being, with its ratio legis to prevent and fi ght against doping in sport, determined its character and most importantly its pluralism. The international community and national legislators have established and implemented the rules in an irregular and unsystematic way, usually in reaction to large-scale public doping scandals. That’s why anti-doping rules in the legal system, in particular in the international legal system, are characterized by legislative chaos. The aim of this article is to describe the pluralism and the diverse character of anti-doping rules in the international law, of both types – binding and nonbinding. The notion of “international law” for the purposes of this article should be understood in a very broad sense, covering also the internal rules of the international sports organizations, even though they are not considered the subjects of the public international law. The article in its opening remarks is focused on the ethical aspects of doping (enumerating the arguments for and against the legalization of doping), its defi nitions and the legal nature of the anti-doping regulations. In the main part of this article the overview of the international antidoping legislation is presented. Namely, the most important ant-doping organizations are described as well as the milestones of their legislation. In this case the main role is played by the World Anti-Doping Agency, the Council of Europe and the UNESCO. Apart from that, the most important legal acts mentioned in the article are the World Anti-Doping Code, the Anti-Doping Convention and the International Convention Against Doping in Sport. Last part of the article is dedicated to the activity of the European Union and the sports organizations in the fi eld of anti-doping. <!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->